Human Resource Retention Practices: from the Employees’ Perspective - Ashraf, Mohammad A.; Joarder, M.H.R.; Masum, R.A. (International Research Journal of Business Studies, 2008)
Employees retention is one of the core challenges faced by many organizations today especially in the corporate sectors of the economy. In this research, a conceptual model was developed and applied in the context of the faculty retention policy of a private university in Bangladesh. The study was conducted primarily to evaluate the current human resource retention practices of the university from the faculties’ point of view. The research identified the core elements of human resource practices, which strongly influence the decision of faculty members to remain in the organization. The result shows that university culture and policies, working environment, teamwork relationship and challenging opportunities are significantly related with the faculty retention policies practiced by the university.